Identification of novel therapeutic targets in acute leukemias with NRAS mutations using a pharmacologic approach - Nonami, Atsushi; Sattler, Martin; Weisberg, Ellen; Liu, Qingsong; Zhang, Jianming; Patricelli, Matthew P.; Christie, Amanda L.; Saur, Amy M.; Kohl, Nancy E.; Kung, Andrew L.; Yoon, Hojong; Sim, Taebo; et al. (AMER SOC HEMATOLOGY, 2015)
Oncogenic forms of NRAS are frequently associated with hematologic malignancies and other cancers, making them important therapeutic targets. Inhibition of individual downstream effector molecules (eg, RAF kinase) have been complicated by the rapid development of resistance or activation of bypass pathways. For the purpose of identifying novel targets in NRAS-transformed cells, we performed a chemical screen using mutant NRAS transformed Ba/F3 cells to identify compounds with selective cytotoxicity. One of the compounds identified, GNF-7, potently and selectively inhibited NRAS-dependent cells in preclinical models of acute myelogenous leukemia and acute lymphoblastic leukemia. Mechanistic analysis revealed that its effects were mediated in part through combined inhibition of ACK1/AKT and of mitogen-activated protein kinase kinase kinase kinase 2 (germinal center kinase). Similar to genetic synthetic lethal approaches, these results suggest that small molecule screens can be used to identity novel therapeutic targets in cells addicted to RAS oncogenes.
Keywords: GERMINAL CENTER KINASE; CANCER-CELLS; INHIBITOR; ACTIVATION; PATHWAY; RAS; POLYPHARMACOLOGY; RESISTANCE; DISCOVERY; SURVIVAL